The Use of Digital Storytelling to Improve Students’ Speaking Ability in Secondary EFL Classroom - Melynda Windy Astuti; Nur Chakim (JELITA, 2023)
The demand of incorporating digital technology into English speaking activities in the secondary EFL classroom is becoming more essential in this digital era. Various teaching strategies have been applied by EFL teachers in enhancing the students’ speaking ability. One of the most popular strategies used by teachers in teaching speaking is using digital storytelling. This research aims to investigate the use of digital storytelling to improve students’ speaking ability in secondary EFL classrooms. A quantitative approach with a quasi-experimental design is employed. This study involves 62 ninth graders in one of state junior high schools in Gresik, East Java. The subjects are obtained through random sampling which are classified into two groups: experimental (31 students) and control groups (31 students). To collect data, speaking pre-test and post-test was used as the research instrument. The findings revealed that the use of digital storytelling as an alternative teaching strategy effectively enhanced the students’ speaking ability. It is proven that the mean score of the experimental group (M= 58.45) is higher than the control group (M= 53.29). Additionally, the Eta-squared which shows the effect size is .63 which means that the utilization of digital storytelling has a large effect on students’ speaking skills. In conclusion, the use of digital storytelling has a positive impact on the secondary EFL students’ speaking ability.